Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1080/0960312031000122460
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of vanadium pentoxide on human peripheral lymphocytes and mucosal cells of the upper aerodigestive tract

Abstract: In addition to tobacco and alcohol consumption, pollutants found in certain industries and in the environment play an important role in carcinogenesis in the upper aerodigestive tract. The aim of the present study was to investigate whether vanadium pentoxide may have a genotoxic effect on human mucosal cells and lymphocytes. The single cell microgel electrophoresis assay (Comet assay) was used to detect DNA damage induced by vanadium pentoxide in human nasal epithelia (n = 11) and in lymphocytes (n = 11). Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…In vitro studies have shown that the metal oxide induces DNA migration in blood cells under standard conditions, but the doses required to cause effects were substantially higher than the plasma concentrations in the workers in the present study (Ivancsits et al 2002; Kleinsasser et al 2003; Rojas et al 1996). Furthermore, results obtained in SCGE experiments with rodents indicate that vanadium compounds cause DNA migration in inner organs (Altamirano-Lozano et al 1996, 1999; Leopardi et al 2005; Villani et al 2007).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In vitro studies have shown that the metal oxide induces DNA migration in blood cells under standard conditions, but the doses required to cause effects were substantially higher than the plasma concentrations in the workers in the present study (Ivancsits et al 2002; Kleinsasser et al 2003; Rojas et al 1996). Furthermore, results obtained in SCGE experiments with rodents indicate that vanadium compounds cause DNA migration in inner organs (Altamirano-Lozano et al 1996, 1999; Leopardi et al 2005; Villani et al 2007).…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, DNA-damaging properties of vanadium compounds have also been found in human and animal cells in vitro (Ivancsits et al 2002; Kleinsasser et al 2003; Migliore et al 1993; Ramirez et al 1997; Rojas et al 1996; Roldan and Altamirano 1990; Zhong et al 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Kleinsasser et al . () reported no cytotoxic effect of vanadium pentoxide in lymphocytes and human mucosal cells. The authors mentioned that cell viability in all the assessments was higher than 80%, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 94%
“…; Kleinsasser et al . ). In addition, information about sex differences after vanadium inhalation exposure is almost inexistent.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation